Instilling values through literature: Analysing Everyman, a medieval morality play - U. Ozen Baykent (Acta Theologica)
War, poverty, hunger, misery, prejudice, loneliness, and intolerance have been the problems of the world throughout history and the sufferings due to these problems have always been deep. In an ever- changing world, characterised by rapid technological advancements, shifting cultural landscapes, and complex global challenges, values education holds paramount importance. This article aims to integrate moral instruction into higher education literature courses, by examining the use of the medieval morality play Everyman as a pedagogical tool. With a growing emphasis on values education and character development, educators are seeking innovative approaches to instil moral principles in learners. The allegorical representation of virtues and vices, the protagonist’s existential journey, and the play’s cultural and historical context contribute to its significance as a catalyst for values education. By delving into the complex moral choices faced by the central character, learners are prompted to contemplate the implications of their own decisions and values.